3D navigation for 3D GIS-initial requirements - Musliman, Ivin Amri; Abdul Rahman, Alias; Coors, Volker (2006)
The needs for three-dimensional (3D) visualization and navigation within 3D-GIS environment are growing and expanding rapidly in a variety of fields. In a steady shift from traditional two-dimensional (2D) GIS toward 3D-GIS, a great amount of accurate 3D data sets (e.g. city models) have become necessary to be produced in a short period of time and provided widely on the market. This requires a number of specific issues to be investigated, e.g. 3D routing accuracy, appropriate means to visualize 3D spatial analysis, tools to effortlessly explore and navigate through large models in real time, with the correct texture and geometry. There had been a lot of study on 3D landscapes, urban and city models. The rapid advancement in science and technology had opened wide options for a change and development of current methods and concepts. Virtual Reality (VR) is one of those developments, which gives the sense of feel in virtual environment. It enables users to visualize, make query and exploring 3D data. Such system can, not only help laymen, who often have trouble in understanding or interpreting complex data, but they also can help experts in decision making. The objective of this paper is to discuss some initial requirements of the proposed solution towards 3D-GIS. Eventually, this paper will serve as a starting point for a more challenging research idea. The focus of this research is to investigate and implementing 3D navigation techniques and solutions for 3D-GIS. Investigation on the support of navigation in real world environment will be carried out. This will include a research on the benefits of using 3D network model (non-planar graph) compared to 2D, how to use visual landmarks in route descriptions and using 3D geometry to get more accurate routing (in buildings, or in narrow street, etc). And as for implementation, a GUI provides the users with means (e.g. fill-out forms) to specify SQL queries interact and visualize 3D outcomes in virtual reality environment. This has opened up the ability to distribute and navigate accurately in 3D virtual worlds. The initial study on Klang Valley will go through data conversion processes from different formats like Laser, VRML, CAD and Shape 3D in a first person view environment using a developed system using VRML, JAVA and .Net compiler. The dataset structure will be in the form of various 2D, 2.5D and 3D array of height fields.